2021
DOI: 10.1080/09613218.2021.1921565
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the adoption of BIM amidst the COVID-19 crisis in China

Abstract: The outbreak of COVID-19 has introduced critical challenges in the architecture, engineering, and construction (AEC) industry; to address these challenges, building information modelling (BIM) can be applied as a project management tool to help enhance collaboration among stakeholders and improve business performance. Amidst the COVID-19 crisis, there is a greater need to explore and implement effective strategies to promote a wider adoption of BIM. However, increasing the willingness of project participants t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 87 publications
0
29
0
Order By: Relevance
“…The impact of COVID-19 was prominent during the search. We found studies conducted for the implementation of IoT, with a focus on the attempt to uphold social distancing [27,59,79,111,119,123,129]. Within this, the usage of building information modelling (BIM) for special design of hospitals, nursing homes, and accommodation was explored.…”
Section: Architecture Sectormentioning
confidence: 99%
“…The impact of COVID-19 was prominent during the search. We found studies conducted for the implementation of IoT, with a focus on the attempt to uphold social distancing [27,59,79,111,119,123,129]. Within this, the usage of building information modelling (BIM) for special design of hospitals, nursing homes, and accommodation was explored.…”
Section: Architecture Sectormentioning
confidence: 99%
“…While the relative advantages of BIM enabled BIM adoption, the complexity of BIM was deemed as a critical inhibitor [54]. The intense manual evaluation suggested that complex BIM adoption circumstances, such as complexities of building characteristics [55] and work processes [56], contractual chal-lenges [57,58], interoperability trends [59], risk factors [55], political and organizational contexts [60,61], dynamics of drivers [62], and emergencies [63], have drawn the interest of many researchers. For instance, Mayouf et al [56] elicited implications of shortfalls impacting 5D BIM adoption as well as complexities facing quantity surveyors within BIM processes in the United Kingdom's construction industry.…”
Section: Qualitative Evaluationmentioning
confidence: 99%
“…Meanwhile, the manual evaluation also revealed that researchers tended to apply useful tools such as adoption impact maps [49], analytical frameworks [9,54], or conceptual models [64] to integrate groups of complex driving and inhibiting factors and willingness and evaluate their impacts on BIM adoption, especially in complex unexpected events. Specifically, Wang et al [63] developed a model to explore the COVID-19 crisis's influence on practitioners' willingness to adopt BIM, which was directly driven by the COVID-19 event criticality and perceived usefulness of BIM. Gurevich et al [49] proposed a BIM adoption impact map that defined a structured process for analyzing complex relationships between public facility agencies' actions, the actions' intermediate impact on designers, contractors, and project managers, and the eventual value added to the occupants.…”
Section: Qualitative Evaluationmentioning
confidence: 99%
“…Nevertheless, all of these actions may be futile unless the construction workers change their behaviour to a more informed and intrinsic culture regarding the importance of health and safety protocols. Furthermore, building information modeling (BIM) in project management may play a vital role in establishing the online transmission and management of information and calls for attention (Wang et al. , 2021c).…”
Section: Implications and Way Forwardmentioning
confidence: 99%